2010
DOI: 10.1590/s0004-28032010000300013
|View full text |Cite
|
Sign up to set email alerts
|

The Montreal classification for Crohn's disease: clinical application to a Brazilian single-center cohort of 90 consecutive patients

Abstract: CONTEXT: Crohn's disease presents very heterogeneous features from a clinical point of view, and classifying Crohn's disease patients in homogeneous subgroups in the light of genetic, molecular and clinical aspects is challenging. The Montreal Classification for Crohn's disease was proposed in 2005 as an effort to characterize Crohn's disease patients according to recent clinical and research advances in the field of inflammatory bowel disease. Since its proposition, the Montreal Classification needs an ample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
3
7
1
2
Order By: Relevance
“…In this study, IBD was found in all ages, but it was most often found between 20 and 25 years of age. These data are similar to those of previously published studies that highlight the age between 15 and 40 years for the occurence of IBD (24)(25)(26)28) . When assessing the age at diagnosis of patients with IBD separately, CD presents only one peak in the age group, unlike the UC, where a second peak is observed between 40 and 44 years of age (28) .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, IBD was found in all ages, but it was most often found between 20 and 25 years of age. These data are similar to those of previously published studies that highlight the age between 15 and 40 years for the occurence of IBD (24)(25)(26)28) . When assessing the age at diagnosis of patients with IBD separately, CD presents only one peak in the age group, unlike the UC, where a second peak is observed between 40 and 44 years of age (28) .…”
Section: Discussionsupporting
confidence: 91%
“…All of these studies were retrospective, with variations in the severity of the patients included, as well as the location of data collection, its scope, type of database used, and form of access to the health system, whether public or private. Although these studies are not comparable owning to their different methodologies, there was a variation in the incidence rate of CD from 3.50 to 6.14/100,000 inhabitants and UC from 2.40 to 7.16/100,000 inhabitants, which demonstrates a chronological increase in the incidence of IBD (9,20,21,24,26) .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…50% of patients underwent surgical procedures and 63% were hospitalized at least once. The authors conclude that the profile of CD in evaluated patients was similar to that described in the literature, and these data were corroborated by other Brazilian authors (Faria et al, 2004;Santana et al, 2008;Torres et al, 2010).…”
Section: Crohn's Disease In Brazilsupporting
confidence: 87%
“…Em relação ao comportamento da DC, segundo a classificação de Montreal, nosso estudo mostrou que o comportamento não penetrante e não estenosante foi o mais comum. Tal achado foi também observado em estudo realizado São José do Rio Preto (São Paulo, Brasil), que constatou frequência de 71% de comportamento não penetrante e não estenosante em um grupo de 90 pacientes com DC (11) . É importante ressaltar, todavia, que o comportamento da DC varia ao longo do tempo e assim, quanto maior o tempo de doença, maior a proporção de comportamento estenosante ou penetrante.…”
Section: Discussionunclassified